2022
DOI: 10.22373/ej.v9i2.10400
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing EFL students’ reading learning process in COVID-19 pandemic through Nearpod

Abstract: This research aims to enhance students’ reading learning process using a genre-based approach during the COVID-19 pandemic through Nearpod. Action research with four stages was applied as a research design. The qualitative data were collected through interviews and teacher’s field notes, while the quantitative data were obtained by students’ reading pre-test and post-test. The qualitative data were analyzed by assembling the data, coding the data, building interpretations, and reporting the outcomes. Meanwhile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Similar results were reported by Hirtz (2020), Pupah &Sholihah (2022) andAbdullah "et al "(2022) who concluded that pupils were positive and motivated about instruction with Nearpod. Nearpod appealed to both intrinsically and extrinsically motivated learners, this includes: High level of interaction -learners enjoy interacting physically with Nearpod; manipulating text; image, matching; dragging and dropping objects; keeping the class on task and raising their self-esteem.…”
Section: Resultssupporting
confidence: 87%
“…Similar results were reported by Hirtz (2020), Pupah &Sholihah (2022) andAbdullah "et al "(2022) who concluded that pupils were positive and motivated about instruction with Nearpod. Nearpod appealed to both intrinsically and extrinsically motivated learners, this includes: High level of interaction -learners enjoy interacting physically with Nearpod; manipulating text; image, matching; dragging and dropping objects; keeping the class on task and raising their self-esteem.…”
Section: Resultssupporting
confidence: 87%
“…The stages of classroom action research from planning, acting, observing, and reflecting conducted in two cycles. Four stages in classroom action research, those are planning, action and observation, and reflection can be applied to seek the problems and find the solution for solving problems in teaching and learning (Pupah & Sholihah, 2022). In planning stage, the researcher plan to implementing Task -Based Learning to improve students' English skills by conducting the steps of Task -Based Learning, namely pre-task, task phase, and language focus.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed and Elmubark (2022) conducted a study that demonstrated a significant difference in the mean scores of the pre-test and post-test, and the students participating in the study were delighted with the application of the Nearpod as an interactive media in the reading teaching-learning process. Pupah and Sholihah (2022) performed a study that proved the efficacy of Nearpod media that successfully supported the reading learning process in class for students because of its user-friendliness, and it enabled teachers to monitor students' progress during the teaching process.…”
Section: Discussionmentioning
confidence: 99%